2016
DOI: 10.1109/access.2016.2537208
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Drones

Abstract: The Internet of Drones (IoD) is a layered network control architecture designed mainly for coordinating the access of unmanned aerial vehicles to controlled airspace, and providing navigation services between locations referred to as nodes. The IoD provides generic services for various drone applications such as package delivery, traffic surveillance, search and rescue and more. In this paper, we present a conceptual model of how such an architecture can be organized and we specify the features that an IoD sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
200
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(235 citation statements)
references
References 18 publications
1
200
0
9
Order By: Relevance
“…Multi-UAV Ad Hoc networks can be applied to achieve above two goals. The multi-UAV network cannot only independently cover the remote areas but also execute many specific tasks (including relay communications, remote sensing, data acquisition, etc [175]). From a global perspective, multi-UAV Ad Hoc networks are required to enable the specified coverage when UAVs fly to remote areas.…”
Section: B Uav-enabled Ioementioning
confidence: 99%
“…Multi-UAV Ad Hoc networks can be applied to achieve above two goals. The multi-UAV network cannot only independently cover the remote areas but also execute many specific tasks (including relay communications, remote sensing, data acquisition, etc [175]). From a global perspective, multi-UAV Ad Hoc networks are required to enable the specified coverage when UAVs fly to remote areas.…”
Section: B Uav-enabled Ioementioning
confidence: 99%
“…Researchers have showed that personal drones are vulnerable to cache-poisoning and buffer overflow that have the potential of causing Denial of Service (DoS) attacks. The penetration tests that were conducted on personal drones like the Wireless Parrot Bebop UAVs revealed the aforementioned vulnerabilities [10], [12], [13]. Some reported cases like the interception of live feeds from US drones by Iraqi militants who managed to access and watch captured videos on their laptops using a $26 worth software shows that even military-grade drones are vulnerable [5], [23].…”
Section: Background Information and Related Workmentioning
confidence: 99%
“…• Once the drone is in a stationary position, i.e., floating at the desired location, the power consumption will rapidly sink [16], [17] and the harvested power can mostly be used for data communication to obtain a required bit-error rate while the remaining power is stored by P charge 2 .…”
Section: System Modelmentioning
confidence: 99%